Towards Low‐Voltage and High‐Capacity Conversion‐Based Oxide Anodes by Configuration Entropy Optimization. Issue 5 (27th December 2022) - Qian, Lizhi; Li, Jinliang; Lan, Gongxu; Wang, Yuan; Cao, Sufeng; Bai, Lu; Zheng, Runguo; Wang, Zhiyuan; Bhargava, Suresh K; Sun, Hongyu; Arandiyan, Hamidreza; Liu, Yanguo
Abstract: Transition metal oxide (TMO)‐based anodes attract much attention for lithium storage due to the merits of high theoretical capacity, facile synthesis, and easy scale‐up. Moreover, the increased working potential avoids the issue of lithium dendrites formation and thus improves battery safety. Herein, we propose a route to significantly improve the electrochemical performance of TMO anodes through configurational entropy optimization. For example, high‐entropy oxide (FeCoNiCrCu)3 O4 is synthesized by carefully selecting metal elements. The (FeCoNiCrCu)3 O4 electrode ensures not only low potential but also holds high capacity. In the half‐cell configuration, the (FeCoNiCrCu)3 O4 electrode provides a specific capacity of 575.7 mAh g −1 after 200 cycles at 0.2 A g −1 . More importantly, the electrode showed a relatively low discharge voltage of 0.39 V at 0.5 A g −1, which is caused by the configuration entropy optimization. The assembled (FeCoNiCrCu)3 O4 //LCO coin‐type full cell exhibits a high capacity of 266.3 mAh g −1 after 100 cycles at 0.2 A g −1 and an operating voltage up to 3.9 V. Abstract : Configuration entropy optimization leads to a high‐performance (FeCoNiCrCu)3 O4 anode with low voltage and high capacity for lithium storage.